Pengaruh Keteladanan Guru Terhadap Kedisplinan Siswa - Nurhidayatullah, Java Ramadhana; Bahrodin, Ariga (TARBAWIYAT, 2024)
Factors that cause student discipline include the teacher's personality which influences the formation of a disciplined and effective classroom atmosphere. The role of the teacher is very important and influential in creating and maintaining a disciplined atmosphere during the learning process in the classroom. However, if this role is not carried out well, this can cause students to become less disciplined. Based on this background, this research aims to determine the influence of teacher example on the discipline of class IV students at MI Al Falah Kuncung Ngoro Jombang. This research adopts a quantitative approach with a survey method. The research subjects consisted of 24 students who participated by filling out a questionnaire. The data collection technique used was a questionnaire with a Likert scale and observation. The collected data was then analyzed using descriptive statistical analysis and nonparametric inferential statistical analysis of rank correlation (Spearman rank) with the help of the SPSS application. The research results show that there is an influence between teacher example and student discipline. This is known from the rank correlation test (Spearman rank) which produces a significance value of 0.000, which is smaller than 0.05. Apart from that, the correlation coefficient of 0.959 shows a very strong positive relationship, meaning that when the teacher's exemplary value increases, student discipline also increases.